Implementasi Metode Prototype Pada Sistem Peminjaman Alat Kerja Berbasis Web Di PT SK Metalindo - ALi Mulyanto; Arjun Gunawan2 (Jurnal informasi dan komputer, 2021)
Method implementation in web-based work tools loan application development is important in assessing the success of the application whether it is running according to plan and has met user requirement. This research will provide an overview of the prototype method in web-based work tools loan application development. The prototype is made with the aim of providing a common perception and initial comprehension from the system will be developed, so that there will be good communication between developer with users. The application to be made web-based with using Laravel framework. The use of Laravel is expected to make it easier to create web-based work tools loan application, so that quality improvement and work tools management be better.